Ecology, History, and Development : A Perspective from Rural Southeast Asia - Hayami, Yujiro (Washington, DC: World Bank, 2014)
The process by which different ecological conditions and historical trajectories interacted to create different social and cultural systems resulted in major differences in economic development performance within Southeast Asia. In the late 19th century, Indonesia, the Philippines, and Thailand commonly experienced vent-for-surplus development through exploitation of unused lands. Nevertheless, different agrarian structures were created. Indonesia s development was mainly based on the exploitation of tropical rain forest under Dutch colonialism. It resulted in the bifurcation of the rural sector between rice-farming peasant proprietors and large plantations for tropical export crops based on hired labor. In the Philippines, exploitation of the same resource base under Spanish rule resulted in pervasive landlessness among the rural population. Relatively homogeneous landowning peasants continued to dominate in Thailand, where delta plains that were suitable only for rice production formed the resource base for development. These different agrarian structures associated with different social value systems have accounted for differential development performance across the three economies in the recent three decades.